Effect of Exogenous Application of Amino Acids L-Arginine and Glycine on Maize under Temperature Stress - Kinga Matysiak; Roman Kierzek; Idzi Siatkowski; Jolanta Kowalska; Roman Krawczyk; Wojciech Miziniak (Agronomy, 2020)
Temperature strongly influences the growth of maize, particularly in the early growth stages. The exogenous application of some amino acids has been proven to have a positive effect on plant growth and development under stressful conditions. The objective of the study was to evaluate the response of maize that was grown under an optimal and stress (fluctuating) temperature to L-Arginine (L-Arg) and Glycine (Gly) application. In the study, it was assumed that the exogenously applied amino acids would alleviate the adverse effects of temperature stress on the maize height, as well as on the biomass of shoots and roots. Ten concentrations of each amino acid from 0.006 mM to 9.0 mM were tested under constant temperature conditions 20–22 °C/23–25 °C (night/day) an fluctuating stress of rising and dropping temperatures between 12–15 °C (night) and 30–38 °C (day). The amino acids were applied to the crop at growth stages V3–V4. In plants that were obtained from seeds pre-treated with L-Arg and Gly, the amino acids increased both the length of radicles and the number of lateral roots. A large discrepancy between the effects of the two amino acids was observed after foliar application. Under optimal thermal conditions, L-Arg increased the mass of shoots and roots by 55–59%. Under stress conditions, root mass was increased even by 100% when compared to the control plants. The best results were recorded at concentrations of 6 mM and 3 mM. Plants that were treated with Gly concentrations generally reached the height of untreated plants or less. It was shown that Gly applied at concentrations of 0.2 mM to 3 mM has a negative effect on the fresh mass of the crop.